Microbiome-Dependent Adaptation of Seaweeds Under Environmental Stresses: A Perspective - Ghaderiardakani, Fatemeh; Quartino, Maria Liliana; Wichard, Thomas (Frontiers in Marine Science, 2020)
The microbiome of macroalgae facilitates their adaptation to environmental stress. As bacteria release algal growth and morphogenesis promoting factors (AGMPFs), which are necessary for the healthy development of macroalgae, bacteria play a crucial role in stress adaptation of bacterial-algal interactions. To better understand the level of macroalgal dependence on the microbiome under various stress factors such as light, temperature, salt, or micropollutants, we propose a reductionist analysis of a tripartite model system consisting of the axenic green alga Ulva (Chlorophyta) re-infected with two essential bacteria. This analysis will allow us to decipher the stress response of each symbiont within this cross-kingdom interaction. The paper highlights studies on possible survival strategies embedded in cross-kingdom interactions that govern the stress adaptation, including general features of metabolic pathways in the macroalgal host or more specific features such as alterations in the composition and/or diversity of bacterial assemblages within the microbiome community. Additionally, we present some preliminary results regarding the effect of recently isolated bacteria from the Potter Cove, King George Island (Isla 25 de Mayo) in Antarctica, on the model system Ulva mutabilis Føyn purified gametes. The results indicate that cold-adapted bacteria release AGMPFs, inducing cell differentiation, and cell division in purified cultures. We propose that microbiome engineering can be used to increase the adaptability of macroalgae to stressful situations with implications for, e.g., the sustainable management of (land-based) aquaculture systems